The effect of income and financial literacy on personal financial behavior: Testing the mediated effect of financial self-efficacy - Wulansari, Dinda Marsela; Heriyadi, Heriyadi; Wendy, Wendy; Giriati, Giriati; Syahbandi, Syahbandi (Institute of Computer Science (IOCS), 2023)
This study aims to determine whether financial literacy and income significantly impact a personal financial behaviour, either directly or through the intermediary factor of financial self-efficacy. Employing Analysis of Moment Structure (AMOS), this study analyses the correlations between independent and dependent variables while considering mediation variables. The data was gathered through a questionnaire distributed to 216 active students chosen via purposive sampling. This research adopts a quantitative approach, utilising primary data from respondent questionnaires and secondary data from the internet and previous academic literature. The findings demonstrate that income and financial literacy positively and directly influence a person's economic behaviour. Furthermore, it has been observed that the relationship between the impact of income and financial literacy on a personal financial behaviour and financial self-efficacy is partially mediated.